Pengaruh Punishmen terhadap Efek Jera Santriwati di Pondok Pesantren Al-Hamidiyah Sawangan-Depok - Annisa Dwi Fitrianingrum; Faza Karimatul Akhlak (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This research is a type of quantitative research conducted at the Al-Hamidiyah Islamic Boarding School in Sawangan Depok, starting from February to July 2019. The population in this study was all female students of class X Al-Hamidiyah Islamic Boarding School in Sawangan Depok, with a sample of 42 female students using the Simple Cluster Random Sampling technique. Data collection using a questionnaire. Instrument analyst technique uses validity and reliability tests. Hypothesis testing using product moment. The results showed that: 1) There is an influence on the implementation of punishment on the deterrent effect of students who violate the rules of the Islamic Boarding School Al-Hamidiyah Sawangan Depok. The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected because the result of "r" count 0.568 is included in the moderate or sufficient category (r count value in the range of 0.40-0.70).